Evaluating reclaimed asphalt mixture homogeneity using force chain transferring stress efficiency. (15th February 2023) - Yang, Xiucheng; Tang, Haizhu; Cai, Xu; Wu, Kuanghuai; Huang, Wenke; Zhang, Qiran; Li, Hao
Highlights: A two-dimensional (2D) finite element model was developed to simulate uniaxial compression tests. DIP technology was used to distinguish the virgin aggregate and RAP aggregate in recycled asphalt mixture. The concept of force chain was introduced to evaluate the homogeneity of mixture. A comparison of the two homogeneity assessment methods reveals different emphases. Abstract: Numerous studies have demonstrated a direct link between the homogeneity of asphalt mixture and the rutting performance, water stability, tensile strength, and service life of the asphalt pavement. Due to the existence of RAP clusters, poor homogeneity of the recycled asphalt mixtures is more severe than natural ones. However, previous studies have mainly focused on analyzing the distribution of aggregates, ignoring the transfer of the internal stress in the mixture. This paper proposed a novel approach for the analysis of the homogeneity of recycled asphalt mixture using the efficiency of force chain transferring stress. Therefore, to prepare gyratory compacted samples, diabase in green color was used as the virgin aggregate and marble in white color as the RAP aggregate. Moreover, to obtain the vertical section images, the samples were cut and processed by digital image processing (DIP). This included distinguishing the virgin and RAP aggregates by global gray threshold segmentation, adding asphalt film around the aggregates, and constructing a force chain network relied on the aggregate contact information. Also, the intensity of the force chain was determined using the finite element method (FEM). In addition, the efficiency of force chain transferring vertical stress ( ETVS ) was introduced and the homogeneity index D of the recycled asphalt mixture was proposed based on the variation coefficient of ETVS. Furthermore, uniaxial compression tests were carried out to mathematically analyze the homogeneity index D proposed in this paper and the homogeneity index D ′ proposed based on the aggregate area ratio in previous studies. The obtained result showed that the homogeneity index D increased first and then decreased with the increase of RAP content. Moreover, the correlation analysis demonstrated the compressive performance of the mixture to be mainly reflected by the homogeneity index D . The correlation coefficients of the compressive strength and the compressive resilient modulus were found to be 0.9010 and 0.8464, respectively. Finally, the homogeneity index D ′ was observed to mainly reflect the stability of the compressive performance of the mixture, with the correlation coefficients of the variation coefficient of the compressive strength and the compressive resilient modulus of 0.8745 and 0.8869, respectively.